The role of smoking in psoriasis - Laguardia, Francesco; Owczarczyk-Saczonek, Agnieszka; Maggi, Paolo (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2024)
Psoriasis has a clear and strong connection with smoking in both its pathogenesis and clinical course. Smoking can cause a serious worsening of both the disease itself and the systemic complications such as cardiovascular events, psoriatic arthritis (PsA), cancer and depression. Smoking also seems to alter the gut microbiota and thus promote psoriasis itself. The aim of our article is to review all the most interesting discoveries on its role and thus provide a good picture of the current state of knowledge. Furthermore, we provide some alternative and healthier coping mechanisms for stress and depression related to the disease such as exercise, meditation, balneotherapy and acupuncture.